INVESTIGATING THE RELATIONSHIP BETWEEN LANGUAGE AND COGNITION AND ITS IMPLICATION ON ENGLISH LANGUAGE TEACHING (ELT) - Pabur, Herminus Efrando; Wardani, Rizqi Claudia; Mokalu, Jenerio Michal; Posumah, Jennie (SoCul: International Journal of Research in Social Cultural Issues, 2024)
There is close connection between language and cognition, in which cognition helps human to acquire language and learn a new language. This present study is conducted to explain the relationship between language and cognition, specifically on the aspects of cognition. This study is also conducted to investigate the implication of the connection between language and cognition on English Language Teaching. This study is a qualitative study with library research method, in which the data sources are the relevant literature such as books, academic papers, and articles from academic journals. Data collection is conducted by collecting and sorting the relevant sources and literature from online database: Scopus, Google Scholar and Sinta. The data obtained are analyzed systematically using the content analysis technique in which the relevant data are quoted to support the core idea of this study. The findings show that there is a close connection between language and cognition, especially how language is closely related to the aspects of cognition. The cognition and its aspects help human in acquiring a language, using the language and evaluating the use of the language. The same also goes to acquiring English as a second or foreign language. It means that there are several implications of the connection of language and cognition toward English Language Teaching (ELT): (1) English language teaching should consider learners' cognition; 2) English language teaching process must be able to attract students' attention; 3) English language teaching must involve memory, reasoning and thinking processes; and 4) English teaching should help students to improve their speaking skills as the observable aspects of cognition.